2017
DOI: 10.1364/oe.25.005509
|View full text |Cite
|
Sign up to set email alerts
|

Modified plastic optical fiber with CNT and graphene oxide nanostructured coatings for ethanol liquid sensing

Abstract: A high sensitivity and simple ethanol sensor based on an un-cladded multimode plastic optical fiber (UCPOF) coated with carbon nanotubes (CNTs) for the detection of different concentrations of ethanol in de-ionized water is developed and demonstrated. The UCPOF probe is fabricated by chemically removing the fiber cladding and integrated with CNT as a sensing layer. The effect of surface morphology on the sensor performance is investigated by characterizing another UCPOF coated with GO nanomaterial. The develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…This change in absorption can manifest as a pure intensity change (no spectral modulation) or as a change in the transmitted light spectrum, e.g., through the appearance of dips or absorption edges in the received spectrum. Many geometrical deformations of optical fibres have been reported in the literature to enhance the sensitivity of absorbance-based ethanol sensors such as U-shaped, coil-shaped, meander-shaped and tapering sensors as well as a combination of bending and tapering sensors [ 35 , 41 , 54 , 55 , 56 ].…”
Section: Optical Fibre Sensing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This change in absorption can manifest as a pure intensity change (no spectral modulation) or as a change in the transmitted light spectrum, e.g., through the appearance of dips or absorption edges in the received spectrum. Many geometrical deformations of optical fibres have been reported in the literature to enhance the sensitivity of absorbance-based ethanol sensors such as U-shaped, coil-shaped, meander-shaped and tapering sensors as well as a combination of bending and tapering sensors [ 35 , 41 , 54 , 55 , 56 ].…”
Section: Optical Fibre Sensing Methodsmentioning
confidence: 99%
“…The sensor exhibited a resolution of 10 −7 Refractive Index Unit (RIU) with 99.76% linearity in the response. The sensitivity and limit of detection (LOD) were found to be 817.76 Optical Density/Refractive Index Unit (O.D./RIU) and 9.2 × 10 −7 RIU, respectively, as shown in Figure 4 b. Khalaf et al showed carbon nanotubes (CNT) to be sensitive to aqueous ethanol solutions in the range of 20% to 100% when they were coated on an unclad multimode POF (UCPOF) using a drop-casting technique [ 56 ]. The GO nanomaterial was also synthesised and used as a sensing layer to obtain a comprehensive view of the CNT-based sensor’s performance.…”
Section: Optical Fibre Sensing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As follows, FBGs consist of a set of narrowband reflectors, having equally spaced grating patterns, inscribed on the optical fiber. The grating period defines the wavelength of the light that is reflected, and the periodic perturbations in the sensors based on FBGs For the production of unclad optical fibers, the fiber cladding can be mechanically removed by the aid of a sharp blade [32], especially in the case of POFs [8], or through chemical etching [57,58], mainly applied in SOFs. Another approach consists in bending the fiber to obtain a U-shaped structure, which allows coupling from the core mode to the cladding modes, enhancing the penetration depth of the evanescent field and consequently the fiber sensitivity [59,60].…”
Section: Grating-basedmentioning
confidence: 99%
“…For the production of unclad optical fibers, the fiber cladding can be mechanically removed by the aid of a sharp blade [ 32 ], especially in the case of POFs [ 8 ], or through chemical etching [ 57 , 58 ], mainly applied in SOFs. Another approach consists in bending the fiber to obtain a U-shaped structure, which allows coupling from the core mode to the cladding modes, enhancing the penetration depth of the evanescent field and consequently the fiber sensitivity [ 59 , 60 ].…”
Section: Theoretical Background On Optical Fiber Biosensing Working Principlesmentioning
confidence: 99%